A CASE OF SYNCHRONOUS PANCREATIC NEUROENDOCRINE TUMOUR IN VON HIPPEL-LINDAU ASSOCIATED PHEOCHROMOCYTOMA - Ismail, Noor Ashikin Binti; Adam, Noor Lita Binti; Karim, Nor Afidah Binti (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Synchronous tumours in adrenal gland and pancreas are rare and considered as part of von Hippel-Lindau (VHL) syndrome. Because pancreatic neuroendocrine tumours (PNETs) in VHL have malignant potential, it is of clinical importance to diagnose these as early as possible. We report a case of synchronous PNETs in pheochromocytoma associated with VHL syndrome managed by surgical excision. CASE A 13-year-old male first presented to an ophthalmology clinic with bilateral eye floaters was found to have classic triad of catecholamines excess symptoms and severe hypertension. Family history was unremarkable except his maternal aunt had ovarian tumour. On examination, his blood pressure was 200/100 mmHg, regular pulse of 120 bpm, normal thyroid, abdominal, and neurological examinations. Fundus examination revealed grade IV hypertensive retinopathy. Electrocardiogram showed significantly increased left ventricular voltages. The diagnosis of clinically suspected pheochromocytoma was confirmed with 24-hour urine normetanephrine at 10 times upper limit normal. CECT adrenal showed lobulated lesion at right suprarenal measuring 5 x 3.6 x 5.4 cm with spontaneous density of 38 HU and absolute washout of 41%. Gallium-68 DOTATATE scan showed moderately avid right suprarenal mass suggestive of pheochromocytoma and intensely avid pancreatic lesion at head of pancreas (1.5 cm) suggestive of synchronous PNETs which was not detected on CT images. There was neither other localizations nor lymph nodes involvement. He underwent right adrenalectomy and pancreatic nodulectomy with complete tumour excision. Genetic analysis revealed a missense mutation c.500G >A (p. Arg167Gln) in exon 3 of the VHL gene. On recent clinic review, he remained asymptomatic and normotensive without medication, and scheduled for follow-up urine metanephrines and MRI brain screening for hemangioblastomas. CONCLUSION Synchronous PNETs in VHL associated with pheochromocytoma are reportedly uncommon. Presence of the exon 3 mutation in VHL gene determines more aggressive course and metastases development of PNETs which requires early detection and intervention.